Visual field bias in hearing and deaf adults during judgments of facial expression and identity - Letourneau, Susan M.; Mitchell, Teresa V. (Frontiers in Psychology, 2013)
The dominance of the right hemisphere during face perception is associated with more accurate judgments of faces presented in the left rather than the right visual field. Previous research suggests that the left visual field bias typically observed during face perception tasks is reduced in deaf adults who use sign language, for whom facial expressions convey important linguistic information. The current study examined whether visual field biases were altered in deaf adults whenever they viewed expressive faces, or only when attention was explicitly directed to expression. Twelve hearing adults and 12 deaf signers were trained to recognize a set of novel faces posing various emotional expressions. They then judged the familiarity or emotion of faces presented in the left or right visual field, or both visual fields simultaneously. The same familiar and unfamiliar faces posing neutral and happy expressions were presented in the two tasks. Both groups were most accurate when faces were presented in both visual fields. Across tasks, the hearing group demonstrated a bias toward the left visual field. In contrast, the deaf group showed a bias toward the left visual field during identity judgments that shifted marginally toward the right visual field during emotion judgments. Two secondary conditions tested whether these effects generalized to angry faces and famous faces and similar effects were observed. These results suggest that attention to facial expression, not merely the presence of emotional expression, reduces a typical left visual field bias for face processing in deaf signers.